Long-term effects of self-reported physical function and disability after participation in an individually adjusted and specific progressive balance training programme for older adults with fear of falling and tendency to fall. (3rd July 2018) - Lindgren, Charlotte; Ståhle, Agneta; Halvarsson, Alexandra
Abstract: Purpose: To evaluate the long-term effects from a 12-week balance-training programme on self-rated physical function and disability in healthy older adults with a tendency to fall and fear of falling. Method: RCT, 59 participants, 67–93 years (42 women). The participants were randomised to an exercise group ( n = 38) and a control group ( n = 21). The intervention consisted of a specific and progressive balance-training programme three times/week for 12 weeks and was evaluated using the Late-Life Function and Disability Instrument (LLFDI) before training, directly after the training period and 6 and 12 months thereafter training. Data were analysed using a mixed model. Results: Significant effects were found regarding physical function: 'Functioning total', 'Basic lower extremity' and 'Advanced lower extremity' in favour for the Exercises group. The exercise group improved significantly from baseline to directly after the training. At the 6 months follow-up, the effects had decreased to values similar to before the training, and remained unchanged until the 12 months follow-up. No significant effects regarding disability were found. The control group remained unchanged over time. Conclusion: No long-term effects were found for physical function or disability assessed with the LLFDI after participation in a specific and progressive balance-training programme for healthy older adults.